2006
DOI: 10.1063/1.2423326
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and electroluminescence of ZnS:Cu,Cl phosphor powder

Abstract: Raman spectra of ZnS:Cu,Cl powders show a structural transition from hexagonal to cubic and a crystal growth with increasing Cu addition (>400ppm), which is supposed to result from Cu incorporation or CuxS precipitation. The redshift of longitudinal optical mode in ZnS:Cu,Cl with increased amounts of Cu suggests that the excess Cu ions were located interstitially in the lattice and created a tensile strain. Under an electric field (3.75×106V∕m), a broad emission spectrum superposing of green, self-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…(1) found in samples A and B was proposed to result from the tensile strain (ε > 0) induced by the interstitial incorporation of Cu ions in the lattice [11]. Therefore, Zn 1−x Cd x S alloys with a specific x can be prepared successfully using this method due to the better atomic diffusion between ZnS and CdS during the solid state reaction at higher temperatures as compared to the chemical methods such as coprecipitation, which suffers from the problem of the different solubility-product constants (K sp ) of CdS (10 −27 ) and ZnS (2 × 10 −25 ) [12].…”
Section: Resultsmentioning
confidence: 97%
“…(1) found in samples A and B was proposed to result from the tensile strain (ε > 0) induced by the interstitial incorporation of Cu ions in the lattice [11]. Therefore, Zn 1−x Cd x S alloys with a specific x can be prepared successfully using this method due to the better atomic diffusion between ZnS and CdS during the solid state reaction at higher temperatures as compared to the chemical methods such as coprecipitation, which suffers from the problem of the different solubility-product constants (K sp ) of CdS (10 −27 ) and ZnS (2 × 10 −25 ) [12].…”
Section: Resultsmentioning
confidence: 97%
“…2, the average size of the phosphor powder was approximately 5µm, indicating that the whole powder particle can be excited by photons with a wavelength of 343nm. However, according to the bipolar field emission model proposed by Fischer [16] and our previous studies [7][8][9], conductive Cu x S precipitates are necessary for luminescent ZnS particles to intensify the electric field and to allow tunneling electrons to recombine with radiation in luminescent centers. This is shown per the dependence of emission intensity on the electric field shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Moreover, the solubility of Cu in ZnS was limited to a constant value, which was less than 400ppm (indicated by the dashed line in Fig. 2) [7][8][9]. Therefore, the Cu near the powder surface beyond the solubility limit was supposed to enter the lattice interstitially (Cu i ), and some will precipitate as Cu x S for the EL.…”
Section: Resultsmentioning
confidence: 99%
“…Excess incorporation of Cu in ZnS has been reported to shift the Raman longitudinal optical (LO) phonon modes. 26 In this case, Cu was incorporated interstitially in the ZnS lattice and induced the tensile stress and structural transformation. 26 Zhang et al, reported a new line at 338 cm −1 identified as the surface optical (SO) phonon mode in ZnS nanowires, which was confirmed by using the dielectric continuum model.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this case, Cu was incorporated interstitially in the ZnS lattice and induced the tensile stress and structural transformation. 26 Zhang et al, reported a new line at 338 cm −1 identified as the surface optical (SO) phonon mode in ZnS nanowires, which was confirmed by using the dielectric continuum model. 27 Self-doping of different catalysts (Au, Sn and Mn) in VLS grown ZnS nanostructures have also resulted in a systematic shift in the LO and surface optical (SO) phonon modes.…”
Section: Introductionmentioning
confidence: 99%